Solution of a discontinuous inverse nodal problem on a finite interval - Koyunbakan, Hikmet; Panakhov, Efibar S. (Pergamon-Elsevier Science Ltd, 2006)
In this paper, the inverse problem of recovering the potential function, on a general finite interval, of a singular Sturm-Liouville problem with a new spectral parameter, called the nodal point, is studied. In addition, we give an asymptotic formula for nodal points and the density of the nodal set. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bessel operator; eigenfunctions; nodal point